The Effect Of Human Resource Quality And Work Motivation On Employee Commitment With Job Satisfaction As An Intervening Variable In Bank Indonesia Representative Offices North Sumatra Province - Ardian Oka; Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
"HR" stands for "Human Resources". The term is generally used in the context of the management of an organization or company to refer to a department or function responsible for managing aspects related to human resources, such as recruitment, training, employee development, performance management, and personnel administration. Human resource management needs to be considered by the leadership of an organization or company in providing maximum service and satisfaction to the community, for that it requires skilled and reliable human resources. The results of this study are as follows: Job Satisfaction has a positive and significant effect on Employee Commitment with the original sample value of 0.303 and p values of 0.004. The quality of human resources has a positive and significant effect on Job Satisfaction with the original sample value of 0.459 and p values of 0.001. The quality of human resources had a positive and insignificant effect on Employee Commitment with the original sample value of 0.222 and p values of 0.052. Work Motivation had a positive and significant effect on Job Satisfaction with the original sample value of 0.443 and p values of 0.002. Work Motivation had a positive and significant effect on Employee Commitment with an original sample value of 0.370 and p values of 0.003. The quality of human resources has a positive and significant effect on Employee Commitment through Job Satisfaction with the original sample value of 0.139 and p values of 0.006. Work Motivation had a positive and insignificant effect on Employee Commitment through Job Satisfaction with the original sample value of 0.134 and p values of 0.055.